Key technologies and development of 5G bearer network - Peiyong MA; Wei WU; Wenqiang ZHANG; Guangming YANG; Feng YANG (Dianxin kexue)
5G will have significant changes in business scenarios,access network,core network and other aspects.It puts forward the requirements of “larger bandwidth,ultra-low delay and high reliability” for bearer network,as well as new requirements for network slicing and flexible networking.Combined with the STN architecture,the key technologies of STN were analyzed,such as SRv6,FlexE,flow detection,intelligent control,etc.,and the STN and SPN were compared,and the specific bearing scheme of STN 5G service was given,which met the differentiated bearing of 5G 2B and 2C services.